Analysis of the Economic Impact and Management Strategies of Health Education Programs on the Formation of Environmentally Responsible Attitudes in Students - Sitorus, Syahrial; Nasution, Monica Angelin; Maulidina (International Journal of Economics and Management, 2023)
Health education programs play an important role in shaping students' attitudes and behaviors towards various aspects of health and well-being. This study aims to analyze the economic implications and management strategies of health education programs in shaping students' environmentally responsible attitudes. Environmental responsibility has become an important concern globally, and education is recognized as a key factor in creating awareness and internalizing sustainable behavior. This research adopted a mixed-methods approach, combining quantitative analysis of economic impacts with qualitative examination of management strategies. The quantitative aspect of the research involved assessing the cost-effectiveness of the health education program, taking into account the resources invested, the benefits derived, and the potential long-term savings due to behavior change. This economic analysis provides insight into the financial viability and potential return on investment of such a program. A qualitative phase explored the management strategies used in a health education program to encourage the formation of environmentally responsible attitudes. Through interviews, surveys, and content analysis, this study investigates how program design, communication methods, resource allocation, and stakeholder engagement contribute to program effectiveness. Results from this study are expected to reveal the economic benefits of health education programs that promote environmentally responsible attitudes in students. In addition, the findings will highlight management strategies that successfully increase the impact and sustainability of the program. By comprehensively understanding the economic dimensions and management aspects, educational institutions and decision-makers can make informed decisions regarding resource allocation and strategy implementation.